Third generation bioethanol from invasive macroalgae Sargassum muticum using autohydrolysis pretreatment as first step of a biorefinery. (October 2019) - del Río, Pablo G.; Domínguez, Elena; Domínguez, Viana D.; Romaní, Aloia; Domingues, Lucília; Garrote, Gil
Abstract: Sargassum muticum, an invasive macroalgae in Europe, was employed as material for third generation bioethanol production. As a first step, autohydrolysis was chosen as an eco-friendly pretreatment, seeking for a high enzymatic susceptibility of the solid phase and high content of hexoses as glucose, galactose and mannose, in both liquid and solid phases, which can be subsequently transformed in ethanol via fermentation. Besides, the search of a minimum consumption of energy in the pretreatment is also a key challenge in bioethanol production. At optimum conditions of autohydrolysis pretreatment, more than 90% of the glucan was recovered in the solid phase (while the other 10% appeared as glucooligosaccharides and glucose in the liquid phase). In the enzymatic hydrolysis carried out with the solid phases, glucan to glucose conversions of 94 and 89% were obtained, with the solid mixed with water and the whole slurry, respectively. Moreover, the whole slurry experiments, where all hexoses present in the raw material (glucose, galactose and mannose) from the solid and the liquid phases are fermented, allows to reach maximum ethanol yields of 80% (14.10 g of ethanol/L) referred to the theoretical yield, in a short time. Highlights: Autohydrolysis is a suitable pretreatment for bioethanol production from Sargassum. Almost 100% of hexoses are recovered in the optimum conditions. Glucan to glucose conversion above 90% was achieved in enzymatic hydrolysis assays. SSF without nutrients reached 80–95% theoretical ethanol yield in less than 10 h.